Application of stable index and transport index for regional air pollution over Twain-Hu Basin - Yue, Yanyu; Bai, Yongqing; He, Huan; Xu, Lin; Chen, Xuan; Zhou, Yue; Tang, Zijun; Zhan, Tian (Frontiers in Environmental Science, 2023)
Affected by stagnant and transmission air pollution, Regional pollution day (RPD) frequently occurs in Twain-Hu Basin. In the winter halfaear of 2015–2021 (November to March of following year), the Regional pollution days reached 331 days. A variety of weather systems together lead to regional air pollution. Based on the observation data of PM2.5 concentration and multi-source meteorological elements during the study period, the weather types of Regional pollution days in Twain-Hu Basin can be divided into four types by using the T-model (T-PCA) classification method, namely, uniform pressure field (42 days), front of cold high-pressure bottom (180 days), back of high-pressure (81 days), and low pressure with an inverted trough field (28 days). Under the influence of uniform pressure field and front of cold high-pressure bottom, it shows the meteorological characteristics of static pollution and transmission pollution, respectively. A stable index (STI) is constructed to describe the PM2.5 pollution caused by the stagnant weather, and a transport index (TRI) is constructed to describe the PM2.5 pollution caused by the transport weather. They have a satisfactory evaluation effect on PM2.5 pollution under the influence of uniform pressure field and front of cold high-pressure bottom, respectively. Interestingly, the correlation coefficients between the pollution index (A stable index + transport index) and PM2.5 concentration could increase obviously to 0.48–0.71 when A stable index and transport index are considered comprehensively. Furthermore, the validation in the winter halfaear of 2021/2022 show that the correlation coefficient of most stations is above 0.70. Therefore, satisfactory performance in validation suggests that this index construction method can be well applied to regional pollution assessment in Twain-Hu Basin.